Entre o balcão e a política: os lojistas de Lisboa e o republicanismo (1890-1910) - Daniel Alves (Ler História, 2010)
The Author examines the role of Lisbon’s shopkeepers in the political and social situation of the final period of the monarchy, a social group where Republicans had ensured a good representation. Developing the issue of the link between small business and Republicanism, a detailed analysis is made on the social and political discourse of Lisbon’s shopkeepers, their class interests, electoral participation and political relationship with the final phase of Monarchy. It was a way to the Republic that began to be shaped in the early 1890s, being established in the first decade of the twentieth century.